2017
DOI: 10.1098/rspb.2017.0278
|View full text |Cite
|
Sign up to set email alerts
|

Trophic state changes can affect the importance of methane-derived carbon in aquatic food webs

Abstract: Methane-derived carbon, incorporated by methane-oxidizing bacteria, has been identified as a significant source of carbon in food webs of many lakes. By measuring the stable carbon isotopic composition (δC values) of particulate organic matter, Chironomidae and spp. and their resting eggs (ephippia), we show that methane-derived carbon presently plays a relevant role in the food web of hypertrophic Lake De Waay, The Netherlands. Sediment geochemistry, diatom analyses and δC measurements of chironomid and remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…''edf'' refers to the effective degrees of freedom known that a substrate competition (for the light isotope, 12 C) can occur when the aquatic primary productivity is high and DIC concentrations are very low (Smyntek et al, 2012), leading to the decrease in the trophic fractionation. Similar observations were previously suggested from sediment records in temperate lakes (Belle et al, 2017b;Schilder et al, 2017).…”
Section: High Elevation Partial Pressure and Isotopic Fractionationsupporting
confidence: 78%
“…''edf'' refers to the effective degrees of freedom known that a substrate competition (for the light isotope, 12 C) can occur when the aquatic primary productivity is high and DIC concentrations are very low (Smyntek et al, 2012), leading to the decrease in the trophic fractionation. Similar observations were previously suggested from sediment records in temperate lakes (Belle et al, 2017b;Schilder et al, 2017).…”
Section: High Elevation Partial Pressure and Isotopic Fractionationsupporting
confidence: 78%
“…First, the attenuation of high flows below dams can influence patterns of autochthonous primary production by modifying the exchange of organisms, nutrients, and detritus between floodplain and river (Cross et al, ; Kennedy et al, ). Second, considerable recycling of both carbon and nitrogen occur within the anoxic stratified layers of impoundments, resulting in the fractionation of stable isotopes producing depleted δ 13 C (Schilder et al, ) and enriched δ 15 N (Burford et al, ) values. Recent measurements from impoundments within the study region demonstrate they produce considerable quantities of methane and NH 4 + , from the anoxic sediments and hypolimnion (Musenze, Werner, Grinham, Udy, & Yuan, ), confirming the potential for carbon depletion and nitrogen enrichment processes to influence stable isotope values of food webs in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…First, the attenuation of high flows below dams can influence patterns of autochthonous primary production by modifying the exchange of organisms, nutrients, and detritus between floodplain and river (Cross et al, 2011;Kennedy et al, 2016). Second, considerable recycling of both carbon and nitrogen occur within the anoxic stratified layers of impoundments, resulting in the fractionation of stable isotopes producing depleted δ 13 C (Schilder et al, 2017) (Musenze, Werner, Grinham, Udy, & Yuan, 2014), confirming the potential for carbon depletion and nitrogen enrichment processes to influence stable isotope values of food webs in these systems. Third, studies have shown that enhanced autotrophic production in large reservoirs can lead to considerable quantities of additional planktonic primary production and organic matter (seston) being exported downstream via releases or spilling events (Marty, Smokorowski, & Power, 2009;Smokorowski et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In modern times, human activities (agricultural practices, sewage water, etc.) have been one of the main drivers of temporal changes in carbon sources sustaining aquatic consumers (Frossard et al ., ; Belle et al ., ; Rinta et al ., ; Schilder et al ., ). The mechanisms by which human activities impact lake carbon cycling often consist of changes in availability of nutrients for aquatic primary production (i.e.…”
Section: Introductionmentioning
confidence: 97%